An Empirical Test on Linkage Between Foreign Exchange Market and Stock Market: Evidence from Hungary, Czech Republic, Poland and Romania - Ngo Thai Hung (European Scientific Journal, ESJ, 2017)
The paper aims to examine the causal relationship between the stock prices and exchange rates in Hungary, Czech Republic, Poland and Romania. The investigation employs Granger’s Causality test and Vector Auto Regression technique on monthly stock return and the foreign exchange rate for the period October 31, 2008 to September 18, 2017. The major findings of the study that there is no Granger’s causality between the exchange rate return and stock return in these countries. The study also uses Vector Auto Regression modeling to confirm that though stock return and exchange rate are related to each other but any consistent relationship does not exist between them. Our results have provided beneficial information for investors, government policies and researchers.